Identifying the Dominant Language of Web Page Using Supervised N-grams - Ng, Choon-Ching; Siau-Chuin, Liew; Wan Muhammad Syahrir, Wan Hussin; Tutut, Herawan (Conference Publishing Services (CPS), 2013)
Natural language processing is an emerging technology in linguistic industry and an aid to human-computer interaction in computer science. Language identification, on the other hand, is a form of pattern recognition that helps to identify predefined language of a web page and to predict the unknown language of one particular text. Written texts are constructed by common features such as character, word and n-gram and these characteristics are unique among languages. From the experiment result, the performance of the supervised n-gram produces an accurate identification value and outperforms the distance measurement on Arabic script web pages.